Misleading Data Bases: An Example from Kidney Transplantation - Pliskin, J. S. (Methods of Information in Medicine, 1977)
In recent years, transplantation survival data have also been documented by whether the patient was nephrectomized or not. Certain conclusions were drawn from the data but the inference contains serious errors in interpretation. This paper attempts to point these errors out, investigate their source, and suggest guidelines for creating a data base from which meaningful conclusions can be drawn. The discussion may be generalized to many other data bases in the medical field.
Keywords: Data Base; Controlled Clinical Trials; Kidney Transplantation; Nephrectomy